Sales Promotion Strategies of Yarn: A Case Study of Dharwad,gadag and Haveri Districts of Karnataka State - Godi, T. N. (Indian Journal of Marketing, 2005)
Textile Industry is the backbone of the national economy. It is contributing 14 percent value additional in the manufacturing sector, one third of the country’s exports earning and 7 percent of the GDP.The spinning and composite mills together were employing about 1 million workers directly and providing employment to nearly 10 crores indirectly. The spinning capacity of India was the largest in the world accounting for about 21 percent of the world’s spindlage. India is the largest exporter of cotton yarn with a share of about 22 percent of the world trade.